Influences of current direction on 1 Hz motor cortex rTMS - Kanig, Carolina; Osnabruegge, Mirja; Schwitzgebel, Florian; Mack, Wolfgang; Schecklmann, Martin; Schoisswohl, Stefan (Brain research bulletin, 2025)
Neuromodulatory changes induced by repetitive transcranial magnetic stimulation (rTMS) are highly variable and lack replicability. Amongst many influencing factors, the current direction of the stimulation is known to affect rTMS aftereffects. In this study, we investigated the influence of current direction on cortical and peripheral markers of motor cortex plasticity as induced by 1 Hz rTMS as well as the correlation of cortical and peripheral markers. Additionally, we investigated possible confounding variables. Twenty-five healthy subjects received 2000 pulses of 1 Hz rTMS at 110 % resting motor threshold intensity over the left motor hotspot inducing anterior-posterior – posterior-anterior (AP-PA) and posterior-anterior – anterior-posterior (PA-AP) current directions in the brain. Motor evoked potentials (MEPs) and transcranial evoked potentials (TEPs) before and after rTMS were assessed with single pulses. Coil placement was ensured by a neuronavigated robot-assisted setup. In sum, 1 Hz rTMS resulted in higher amplitudes of MEPs and TEP components N15, N45 and P60 and a reduced amplitude of N100, whereby the induced PA-AP current direction in the brain elicited higher effects. MEP and TEP N15 latency were prolonged and N100 shortened after rTMS. PA-AP current direction elicited stronger changes in latency for MEPs and N15. N45 and MEP correlated in the PA-AP pre rTMS condition with negligible effect size. Our findings of facilitatory pre-to-post rTMS changes are in contrast to preliminary assumptions that 1 Hz rTMS acts inhibitory. However, since high variability and low reliability of rTMS aftereffects are prominent in the current literature, these results shed light that potential influencing factors need to be better reported, controlled and investigated. We suggest to further investigate effects of stimulation intensity and tiredness of subjects on rTMS. We were able to replicate current direction effects which strengthens the hypothesis of activation of different sets of neurons. •1 Hz rTMS at 110 % RMT with 2000 pulses over the motor cortex acted excitatory.•AP-PA and PA-AP induced current directions resulted in the same direction of 1 Hz rTMS aftereffects.•PA-AP induced current direction elicited larger 1 Hz rTMS aftereffects than AP-PA.•MEPs and TEPs were not meaningfully correlated.